LEAPS of faith- exploring development and implementation of a longitudinal curriculum focusing on mental health, leadership, altruism,ethics and EDI, Professional Identity Formation for medical and dental students - Komal Atta; Tazmeen Kaukab; Fatima Amin; Ahmad Atta (Journal of University Medical & Dental College)
Abstract